The relationship of live-streaming companies and online content creators from the perspective of Polish employment law - Przewoźniak, Ryszard (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
Internet-based sites granting access to live-streaming services and broadcasts, aimed at wide spectrum of viewers are constantly evolving, creating new means of engaging both viewers, and creators alike. One of the symptoms of such evolution is a shift towards more mutually binding legal situation between live-streaming platforms and creators of live-streams. This change could be observed from the economical point of view, as well as analysing obligations both parties agree upon at the start of monetisation of ones broadcasting activity. These legal contracts show a tendency to present live-streaming as a sort of employment, both in their form and type of obligations created. This text presents an analysis of said contracts, as well as relationships between streaming platforms and streamers as a whole, to outline and dissect its resemblance to ones found in more common types of employment. During the analysis, authors aim is to describe position of live-streamers in case of dispute between them and a platform, as well as to present the methods of protection against unfair termination of any such agreement. This will be presented in context of more widely understood employment law, as well as various initiatives regarding legal coverage of non-traditional forms of employment, such as platform work. The summary of this analysis, will be focused upon dispute regarding possibility, and, in further context, necessity of creating a strong regulation of this type of activity in context of employment law. Said dilemma will be analysed with context of wide popularity of other, alternative types of employment relationships, such as business to business agreements, widely applied in certain professions. This summary will be accompanied by a general overview of the condition of modern employment standards in the digital age.